Electron flow dynamics in resistive gap - Pashchenko, A.; Ostroushko, V. (Вопросы атомной науки и техники, 2017)
It is considered the evolution of electron flow in the short-circuited gap with taking into account of the braking force proportional to velocity. The linear analysis of the stationary states stability is made. For the states with a small instability increment it is considered the nonlinear evolution of perturbation. The numerical simulations of the transitions from the unstable modes to the stable ones with the removing of the charge surplus from the gap are carried out.